The Quantum Mechanics of Israeli Totalitarianism. (1st April 2016) - ,
Abstract : This article argues that Israel's occupation of Palestinian territory represents criminalized state behaviour at the most systematic, intricately planned and executed. Evoking the quantum physics of Israel's matrix of control, the article argues that to understand how it feels to live as a Palestinian today requires the mindset of a particle physicist, not a social scientist. Life in Israel/Palestine involves negotiating a host of forces over which the average Palestinian has as much control as the average electron or proton does over the nuclear and quantum forces determining its path. The power embodied in Israel's matrix of control lies in the state's ability to shift rules, tactics, amplitude and frequency of the forces, strategies and techniques and technologies of occupation. The article argues that the Occupation and the conditions it creates have become normalized, and that maintaining a situation of confusion and ambiguity is key to making the Occupation effectively permanent.